THE DATA COLLECTION PROCESS BPKB APPLICATIONS IN FINANCE PT.PARAMULTI USING VISUAL BASIC 6.0 - Diyah Mayasari; Irfan, SKom, MMSI Irfan, SKom, MMSI (Jurnal Sistem Informasi, 2009)
At this time the increasing development of computer technology, technology capable of providing accurate information and accurately so that no doubt again. For example on PT. Paramulti Finance in handling the data collection process which is still manually BPKB in providing consumer finance will spend a long time completion, especially concerning the problem statement. This program includes the application of credit payment information each time transaction, so it can be more easily and to optimize control of every month. With the help of supporting applications created with Microsoft Visual Basic 6.0 is expected to ease the credit payment information to know.